PENENTUAN AWAL DAN AKHIR MASA ‘IDDAH OLEH PENGHULU DALAM BINGKAI KEARIFAN LOKAL HUKUM KELUARGA ISLAM - Rahmania Kusumawati , Ita; Nisak, Khoirotun (USRATUNA: Jurnal Hukum Keluarga Islam, 2024)
The waiting period that women undergo after divorce or the death of their husband ('iddah) is regulated by religion in sharia law. The length of this waiting period varies depending on the case (living divorce or dead divorce). There are cultural differences regarding determining the iddah period using a divorce certificate dated AD and Hijri, which then gives rise to legal problems regarding the application of these provisions in various Religious Affairs Offices (KUA). With a qualitative approach and data taken through observation, interviews, and documentation, this can be overcome because religious law (Compilation of Islamis Law or KHI) and culture law (local wisdom) are interrelated. The results of the research show that the eight (KUA) in Jombang Regency all determine the start of the 'iddah period from the termination of a case in the divorce deed, and for women whose husband dies, the first day of iddah is the day of the husband's death. In practice, the eight KUAs in Jombang Regency do not have obstacles related to culture and local wisdom in interpreting the 'iddah period because all elements in the KUA have agreed not to provide personal interpretations and opportunities to differ in opinion, although in its implementation in society there are still several conditions. which causes difficulties for women in carrying out the 'iddah period, such as economic helplessness and lack of support from ex-husbands or families of women who are undergoing the 'iddah period.